Systematic mapping study of climate change mitigation: a review of public administration studies - Santoso, Iman; Rifani, Denny Nazaria; Tando, Cahyoko Edi (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Climate change is a critical issue that is constantly discussed in numerous international forums, particularly considering its wide-impact and cross-sectoral nature. Every aspect of real life, especially the environment, is impacted by this global phenomenon, hence the need for real solutions from various groups. Public administration scientists saw this as a problem that must be solved through several literature studies conducted. This research method will use a systematic mapping study using the Taylor and Francis Group database that has been determined. The results of this study with 3 actors combined with collaborative governance show that government actors focus on domestic and foreign policies adopted by emphasizing the collaboration between government agencies that can be done. Meanwhile, the private sector has a unique contribution where they implement a circular economy and mutual cooperation determined by the principle of humanism and remain humane by helping the community. Meanwhile, community actors emphasize the existence of local knowledge and community capacity as knowledge resources in climate change adaptation. This research shows the interplay among actors in climate change mitigation and encourages future researchers to provide a connection to decision-making. Current trends suggest that the public and private aspects of climate change mitigation currently lack synergy, with each of the key governance actors working separately to mitigate climate change.